i-Care: A Web-Based Online Goods Donation Management System - Nur Izzah Batrisyia Mohd Azhar; Mazidah Mat Rejab (Applied Information Technology And Computer Science, 2023)
Emergencies are described as urgent situations that have imminently threatened lives or livelihoods. For example, flooding. Hence, many people donate their useful goods with the aid of NGOs to help victims. However, dumping goods into these devastated areas has stymied relief efforts. Supplies needed by victims are often insufficient. Additionally, NGOs manual data management process is time and energy consuming. Therefore, a system entitled ’’I-Care: A Web-Based Online Goods Donation Management System’’ is to be developed. The system offers a structured management platform with a focus on emergency relief assistance. It is designed using an object-oriented approach and a System Prototyping Model as its methodology. It is expected to allow donors to donate their goods according to the goods category set by the administrator. Meanwhile, administrators are allowed to update the goods specifications needed by victims. Furthermore, it simplifies the NGO’s task of recording the whole donation activity and processes.